2011
DOI: 10.4238/vol10-3gmr1148
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA variation of the critically endangered hawksbill turtle (Eretmochelys imbricata) nesting on Iranian islands of the Persian Gulf

Abstract: ABSTRACT. Genetic diversity of sea turtles (hawksbill turtle) was studied using sequencing of mitochondrial DNA (mtDNA, D-loop region). Thirty dead embryos were collected from the Kish and Qeshm Islands in the Persian Gulf. Analysis of sequence variation over 890 bp of the mtDNA control region revealed five haplotypes among 30 individuals. This is the first time that Iranian haplotypes have been recorded. Nucleotide and haplotype diversity was 0.77 and 0.001 for Qeshm Island and 0.64 and 0.002 for Kish Island,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…We also documented the first sharing of a nesting haplotype across the entire expanse of multiple ocean basins, with haplotype EiIP33 (not found in the Atlantic) spanning from the westernmost Indo‐Pacific Ocean (i.e., Indian Ocean) to the EP Ocean (Tabib et al. ; Vargas et al. ; this study).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We also documented the first sharing of a nesting haplotype across the entire expanse of multiple ocean basins, with haplotype EiIP33 (not found in the Atlantic) spanning from the westernmost Indo‐Pacific Ocean (i.e., Indian Ocean) to the EP Ocean (Tabib et al. ; Vargas et al. ; this study).…”
Section: Discussionsupporting
confidence: 56%
“…3) for hawksbills in the EP suggest the species likely radiated out of the Indo-Pacific on a relatively recent evolutionary timescale (Gillespie 1984). We also documented the first sharing of a nesting haplotype across the entire expanse of multiple ocean basins, with haplotype EiIP33 (not found in the Atlantic) spanning from the westernmost Indo-Pacific Ocean (i.e., Indian Ocean) to the EP Ocean (Tabib et al 2011;Vargas et al 2015;this study). The presence of this haplotype in nesting populations across these ocean basins further supports a recent radiation.…”
Section: Evolutionary History and Phylogeographymentioning
confidence: 58%
“…Phylogeographic studies of hawksbill turtles have been performed apart for populations in Brazil (Lara-Ruiz et al, 2006;Vilaça et al, 2013;Proietti et al, 2014), Caribbean (Bass et al, 1996;Troëng et al, 2005;Bowen and Karl, 2007;Velez-Zuazo et al, 2008;Blumenthal et al, 2009;Richardson et al, 2009;Browne et al, 2010;LeRoux et al, 2012;Carreras et al, 2013;Wood et al, 2013;Gorham et al, 2014;Trujillo-Arias et al, 2014;Cazabon-Mannette et al, 2016;Hill et al, 2018;Labastida-Estrada et al, 2018), Eastern Atlantic (Monzón-Argüello et al, 2010Putman et al, 2014), Indo-Pacific (Vargas et al, 2016), Persian Gulf (Tabib et al, 2011(Tabib et al, , 2014Natoli et al, 2017), Eastern Pacific (Gaos et al, 2012(Gaos et al, , 2016(Gaos et al, , 2017(Gaos et al, , 2018Zuniga-Marroquin and Monteros, 2017), Southeast Asia (Nishizawa et al, 2016) and Japan (Nishizawa et al, 2010). The first genetic studies used mtDNA control region data based on approximately 300 bp sequences (Bass et al, 1999;Dias-Fernández et al, 1999;Troëng et al, 2005;Bowen and Karl, 2007;Nishizawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adults travel hundreds or thousands of kilometres from foraging sites to the breeding regions (Van Dam et al ., 2008). Various studies have shown that only green and hawksbill turtles breed in the Persian Gulf coasts, while other species come to these coasts for feeding and grazing (Valavi, 1993; Saeedpour et al ., 2003; Mobaraki & Elmi, 2005; Moghimi et al ., 2009; Tabib et al ., 2011). Eretmochelys imbricata is the only species which was observed laying eggs in the Kish Island coast.…”
Section: Discussionmentioning
confidence: 99%